A New Proof of Inequality for Continuous Linear Functionals. (14th March 2011) - Cui, Feng; Yang, Shijun
Abstract : Gavrea and Ivan (2010) obtained an inequality for a continuous linear functional which annihilates all polynomials of degree at mostk - 1 for some positive integerk . In this paper, a new functional proof by Riesz representation theorem is provided. Related results and further applications of the inequality are also brought together.